Green Tea Yogurt Supplemented with L. paracasei E1 Microcapsules Increases Erythrocyte Counts and B Cell Development in High-Fat Fructose Diet Mice - Sa'adah, Nur Alfi Maghfirotus; Ardiansyah, Esha; Fadlilah, Dawama Nur; Izati, Rahmi; Al-Faizah, Belinda Nabiila; Kavitarna, Septhyanti Aprilia; Atho’illah, Mochammad Fitri; Arifah, Siti Nur; Jatmiko, Yoga Dwi; Tsuboi, Hideo; Rifa'i, Muhaimin (Cell and BioPharmaceutical Institute, 2025)
Background: Obesity-induced inflammation causes hematopoietic stress, disrupting bone marrow homeostasis. Green tea yogurt supplemented with Lacticaseibacillus paracasei E1 microcapsules (GTYP) is a promising way to overcome obesity due to its high antioxidant and anti-inflammatory activity. However, GTYP effects on blood production, specifically erythrocytes and B cells, remain unexplored.Materials and methods: Male Balb/C mice were fed either a high-fat fructose diet or a normal diet for 12 weeks. Microencapsulation was done by double coating of alginate-chitosan. There were seven groups in this study: normal diet (ND), high-fat fructose diet (HFFD), HFFD with 1.3 mg/kgBW Simvastatin (T1), HFFD with 5 g/kgBW plain yogurt (T2), HFFD with 2.5 g/kgBW GTYP (T3), HFFD with 5 g/kgBW GTYP (T4), and HFFD with 10 g/kgBW GTYP (T5). Erythrocyte counts from the peripheral blood were taken weekly. After 28 days of treatment, mice were sacrificed, bone marrow (BM) and lymphocytes were isolated. The cells of Ter119+, Ter119+CD59+, and B220+SDF-1+ were measured using flow cytometry.Results: HFFD not only reduces the peripheral erythrocyte count (2.15×109 cell/mL) but also affects the hematopoietic system, depleting Ter119+ (11.76%), TER119+CD59+ (0.050%), and B220+SDF-1+ (0.465%). Mice receiving 5 g/KgBW GTYP improved erythrocyte count (9.95×109 cells/mL). The parameters of erythrocyte and B cell development showed more remarkable improvement with GTYP treatment than simvastatin and plain yogurt (p<0.05). Molecular docking also indicated a great inhibitory effect of EGCG (-7.7) for the CXCR4 receptor.Conclusion: GTYP can potentially increase erythrocyte count and B cell development, particularly under obese conditions. Keywords: anti-obesity, B lymphopoiesis, erythrocyte count, green tea yogurt, probiotics